Superfast Zincophilic Ion Conductor Enables Rapid Interfacial Desolvation Kinetics for Low‐Temperature Zinc Metal Batteries - Xiaomin Cheng; Yinze Zuo; Yongzheng Zhang; Xinyu Zhao; Lujie Jia; Jing Zhang; Xiang Li; Ziling Wu; Jian Wang; Hongzhen Lin (Advanced Science, 2024)
Abstract Low‐temperature rechargeable aqueous zinc metal batteries (AZMBs) as highly promising candidates for energy storage are largely hindered by huge desolvation energy barriers and depressive Zn2+ migration kinetics. In this work, a superfast zincophilic ion conductor of layered zinc silicate nanosheet (LZS) is constructed on a metallic Zn surface, as an artificial layer and ion diffusion accelerator. The experimental and simulation results reveal the zincophilic ability and layer structure of LZS not only promote the desolvation kinetics of [Zn(H2O)6]2+ but also accelerate the Zn2+ transport kinetics across the anode/electrolyte interface, guiding uniform Zn deposition. Benefiting from these features, the LZS‐modified Zn anodes showcase long‐time stability (over 3300 h) and high Coulombic efficiency with ≈99.8% at 2 mA cm−2, respectively. Even reducing the environment temperature down to 0 °C, ultralong cycling stability up to 3600 h and a distinguished rate performance are realized. Consequently, the assembled Zn@LZS//V2O5‐x full cells deliver superior cyclic stability (344.5 mAh g−1 after 200 cycles at 1 A g−1) and rate capability (285.3 mAh g−1 at 10 A g−1) together with a low self‐discharge rate, highlighting the bright future of low‐temperature AZMBs.